Mother’s Baby, Father’s Maybe – Intestate Succession: When Should a Child Born Out of Wedlock Have a Right to Inherit from or Through His or Her Biological Father - Davison, Camille M. (Columbia Journal of Gender and Law, 2011)
When the renowned chess genius Bobby Fischer died, his body was exhumed in order to determine whether his genetic samples matched samples from a child whose mother claimed he fathered outside of a marital union. Bobby Fischer was domiciled in Iceland and under Icelandic law, if there had been a genetic connection, the child would have been the sole legal heir of his intestate estate. The law is not so clear in the United States. Each state has enacted laws of intestate succession. While the laws in all fifty states provide that a child born out of wedlock is automatically his or her mother’s legal child, state statutes vary substantially as to when that same child is entitled to an intestate inheritance from or through his or her genetic father. If Fischer, the Chicago native, had been domiciled in North Carolina at his death, even if DNA had established a genetic relationship between Fisher and the child, the child would still have been precluded from inheriting her father’s estate. In North Carolina, a biological or genetic connection is not enough to constitute a paternal legal heir without strict compliance with statutory formalities. In contrast, if Fischer had been domiciled in Georgia, and through clear and convincing evidence a genetic relationship was established, the child would inherit from her father’s estate as his legal child. As one can see, in the United States, paternal inheritance depends on the state of the father’s domicile. As such, when we discuss the out of wedlock child and his or her right to inherit family wealth through intestate succession, the old adage “Mother’s baby,father’s maybe” comes to mind. In this paper, I suggest that each of the fifty states should, like Georgia and other similarly situated states, follow the trend of Icelandic law in the area of intestate succession. Specifically, where clear and convincing evidence (either before or after afather’s death) determines that a father is the genetic parent of a child, and there has been no formal adoption of the child, such child should be entitled to an intestate share of his or her father’s estate in the same manner as a child born to a married parents.